Evaluating normalisation: An argument-based approach. (July 2019) - Yoon, Sook Jhee; Gruba, Paul
Abstract: Now integral to our daily lives, the use of networked technologies is an expected part of modern language teaching. Grounded in concepts set out by Bax, we set out an argument-based approach to examine the constructive alignment of digital materials and learning outcomes in a blended modern language program. Through participatory action research, document analysis and stakeholder interviews, we focus on the ways that materials are understood and used by language educators and students alike. Analysis of the data points to areas of moderate support for the claim that normalization has been achieved, and mismatches are particularly prominent in the realm of stakeholder expectations. Importantly, the paper contributes to a view that a focus on blended materials provides insights into the processes of normalisation, and may well be predicated on the constructive alignment of materials design and learning outcomes.